Analysis of Commissive, Directive and Expressive Speech Acts in the Film the God Father Director Francis Ford Coppola - Marlianda, Rendi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The God Father is a 1972 American crime film, directed by Francis Ford Coppola and with a screenplay by Mario Puzo and Coppola. The aim of this research is to describe commissive, directive and expressive speech acts in the film The Godfather. The research method uses a qualitative descriptive method. The data collection technique used is documentation technique. Data analysis techniques include description, classification, analysis, data interpretation, evaluation and conclusion stages. The results of this research show that there were 9 types of commissive speech acts found in the film The God Father, 5 in promising utterances, and 4 in swearing utterances. In the directive speech in the film The God Father, 26 types of speech were found, 7 in pleading speech, 2 in demanding speech, 10 in suggesting speech, and 7 in challenging speech. In the expressive speech in the film The God Father, 20 types of speech were found, 10 were praise speech, 4 were thanking speech, 3 were criticizing speech, and 3 were complaining speech.